Compliance and stability of INR of two oral anticoagulants with different half-lives: a randomised trial - Laporte, Silvy; Quenet, Sara; Buchmüller-Cordier, Andréa; Reynaud, Jacqueline; Tardy-Poncet, Brigitte; Thirion, Christine; Decousus, Hervé; Mismetti, Patrick (Thrombosis and Haemostasis, 2003)
The aim of the study was to assess the respective roles of the half-life of elimination of oral anticoagulants and patient education as causes of instability of anticoagulation level in patients on oral anticoagulant therapy. Patients were randomised to receive either warfarin (long half-life) or acenocoumarol (short half-life) and either intensive or standard education, according to a factorial design. Instability of oral anticoagulant therapy was evaluated by the percentage of INRs and the time within the target range, and the variability between successive measurements. Compliance was assessed by means of electronic pill bottles. Eighty-six patients were included. Apart from the variability index, instability was similar between groups. Correlations between compliance and instability were observed only in the acenocoumarol group. No difference was found between the education groups. In patients starting oral anticoagulant therapy, dose determination may be the most important factor contributing to instability.
Keywords: Warfarin; acenocoumarol; compliance; instability; patient education